Ethics : discovering right and wrong - Pojman, Louis P. (Boston, MA : Wadsworth, 2012)
This book offers a concise yet comprehensive overview of the fundamental objectives and outlooks of ethical theory. The book challenges readers to develop their own moral theories and to reason through ethical problems for themselves. The text even-handedly raises critical questions and fosters independent thinking within a rigorous presentation that draws numerous examples from both classical and contemporary sources. This edition maintains the text's clarity and strengths with its non-dogmatic style and generous presentation of various positions. This revision includes more feminist and multicultural ethical perspectives.
What is ethics? -- Ethical relativism -- Moral objectivism -- Value and the quest for the good -- Social contract theory and the motive to be moral -- Egoism, self-interest, and altruism -- Utilitarianism -- Kant and deontological theories -- Virtue theory -- Gender and ethics -- Religion and ethics -- The fact-value problem -- Moral realism and the challenge of skepticism.
Includes bibliographical references and index.
Keywords: Ethics; Ethics